2009
DOI: 10.1111/j.1365-263x.2009.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with caregivers’ perception of children's health and oral health status: a study of 6‐ to 36‐month‐olds in Uganda

Abstract: The results support the growing recognition of oral health as a predictor of health and well-being in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 26 publications
3
43
1
4
Order By: Relevance
“…A total of 86% of the parents reported their children presented impact for at least one item in the child section, and 74% reported impact for the family section, such frequencies were higher than those found in other studies 3,15,18 . When the frequency of impact for each ECOHIS item was assessed, "pain in teeth, mouth or jaw" was the most frequently reported item for the child section, followed by the item of "difficulty in eating some foods".…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…A total of 86% of the parents reported their children presented impact for at least one item in the child section, and 74% reported impact for the family section, such frequencies were higher than those found in other studies 3,15,18 . When the frequency of impact for each ECOHIS item was assessed, "pain in teeth, mouth or jaw" was the most frequently reported item for the child section, followed by the item of "difficulty in eating some foods".…”
Section: Discussioncontrasting
confidence: 43%
“…According to previous studies with preschool children, the presence of dental caries based on clinical examination was strongly associated with the child's OHRQoL 17,18,[23][24][25] . This finding was confirmed when the reason for seeking dental care was considered; parents who affirmed taking the child for caries treatment had the worst ECOHIS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that the presence of ECC affects the quality of life of children [29,[33][34][35]. According to Low [35], children affected by dental caries do not necessarily complain of pain and can manifest their effects through changes in eating and sleeping habits.…”
Section: Discussionmentioning
confidence: 98%
“…Low income [29][30][31] and low educational level [11,32] are considered risk factors to a poor quality of life. It was found that mothers with low schooling had a relative risk of 1.37 for poor perception of child's OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers have more influence on the child because they are more present as a caretaker, and when they are well instructed by healthcare practitioners, can form attitudes and behaviours and transform them into generation of healthy habits 1,2 . Dental caries is the most prevalent chronic disease in the infancy, being classified even as a "pandemic" condition characterised by a high rate of untreated cavities, thus causing pain, distress and functional restrictions among the children 3 .…”
Section: Introductionmentioning
confidence: 99%